High Resolution SCB Scheme for Hyperbolic Systems of 2-D Conservation Laws (Journal of Computational Mathematics, 1998)
In this paper, a new class of high resolution schemes satisfying the "condition A" (SCA) and the "condition B" (SCB) for hyperbolic systems of conservation laws in one and two dimensions are constructed. Moreover, the results of the numerical experiments by using these schemes are given for the system of Euler equations in one and two dimensions.